THE IMPACT OF SOCIAL MEDIA ON CONSUMER INNOVATION - Kurbanbaeva Iroda Timurovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation: This thesis investigates the transformative impact of social media on consumer innovation, particularly focusing on how these platforms facilitate an interactive dialogue between consumers and brands. Social media has emerged as a pivotal tool for engaging consumers directly, allowing them to influence product development and innovation actively. This research explores various dimensions of this interaction, including the role of consumer feedback in shaping product decisions, the effectiveness of social media strategies in fostering consumer loyalty, and the overall impact on the innovation lifecycle of products.